Angiotensin-converting enzyme inhibitory activity of four Amadori compounds (ACs) and mechanism analysis of N-(1-Deoxy-D-fructos-1-yl)-glycine (Fru-Gly). (1st April 2022) - Zhou, Renjie; Yang, Cheng; Xie, Ting; Zhang, Jian; Wang, Chenqiang; Ma, Ziqiang; Zhang, Lianfu
Abstract: Amadori compounds (ACs) are the first stable product formed in the initial stage of the Maillard reaction and are widely present in processed foods. In addition to being widely known as the flavor precursors, ACs have attracted attention in recent years because many functions have been revealed, including ACE inhibition. In this work, we synthesized four ACs ( N -(1-Deoxy-D-fructos-1-yl)-glycine (Fru-Gly), N -(1-Deoxy-D-fructos-1-yl)-proline (Fru-Pro), N -(1-Deoxy-D-fructos-1-yl)-serine (Fru-Ser) and N -(1-Deoxy-D-fructos-1-yl)-threonine (Fru-Thr)) and characterized them using UPLC-Q-TOF-MS spectra. The four ACs' angiotensin-converting enzyme (ACE) inhibitory activities were verified for the first time, the IC50 value range was 1.447–4.204 mmol/L, the Fru-Gly has the best effect. And all the four ACs showed good digestion stability, the content remained above 70% after 5 h of continuous digestion simulation. In order to reveal the mechanism of ACs inhibiting ACE, we selected Fru-Gly, beacuse of the best inhibitory effect, to carried out enzyme kinetics, circular dichroism spectroscopy, fluorescence spectroscopy, thermodynamics and molecular docking analysis. The results showed that Fru-Gly was a noncompetitive inhibitor, it spontaneously binds to the inactive site of ACE by hydrogen bond and causes the conformation change of ACE to inactivate it. The reaction is easier to proceed at low temperatures. Graphical abstract: Image 1 Highlights: ACs' main characteristic fragment ions are [M+H] +, [M + H–H2 O] + and [M + H–2H2 O] + . Four ACs have the excellent digestive stability. Fru-Gly has the best ACE-inhibitory activity among four ACs. Fru-Gly is a noncompetitive inhibitor, bonding to the ACE by H bond spontaneously. Fru-Gly can cause fluorescence quenching and structure change of ACE molecule.